ASPEK BIOLOGI IKAN SIRO (Amblygaster sirm) BERDASARKAN DATA DI PELABUHAN PERIKANAN PANTAI TASIKAGUNG, REMBANG - Celine Anjar Sari; Suradi Wijaya Saputra; Wiwiet Teguh Taufani (JURNAL PERIKANAN TROPIS, 2021)
Spotted sardinella is one of small pelagic fish with high economic protein and it has been caught by mini purse seine. In fact, Spotted sardinella has a large number of catches which can endanger their sustainability in Java Sea. The purpose of the study was to find out the length of first caught, length and weight relationship, growth parameters, mortality rate, and exploitation rate of spotted sardinella. The method used was survey method. The data were collected once in every 1 month during August until November 2021 at Tasikagung Fishery Port. The primary data collected were fish total length (mmTL) and fish weight (g). The result of the study revealed that size structure of fish ranged from 120-205 mmTL and length first capture 170 mmTl. The length-weight relationship analysis was W =   0,00000571 L 3,54  with positive allometric growth pattern. The growth parameters by Von Bertanlanffy was Lt = 206,5(1-e-0,95(t+0,00266)) and it was categorized as fast growth. The fishing mortality and natural mortality were 1,71 year-1 and 1,01 year-1. The exploitation rate was 0,63 year-1, which means sardinella has been exploited.